Preparatory knee flexion movement facilitates faster sideways jumping execution in male collegiate soccer goalkeepers - Fujimoto, M.; Sato, M.; Nagano, A.; Rogers, M. W.; Isaka, T. (Sports Biomechanics, 2023)
Preparatory lower-limb loading conditions may affect the jump-to-reach performance of soccer goalkeepers. This study investigated the effect of pre-jump lower-limb loading/unloading during bilateral knee flexion-extension movements on sideways jump-to-reach performance in 18 male collegiate soccer goalkeepers. Participants performed the two-choice (high and low targets) reaction-time single-leg jump-to-reach task under two conditions: without preparatory movements (no-prep) and with continuous alternating knee extension and flexion movements (prep). The `go` cue was provided with different preparatory loading conditions during the pre-jump knee extension and flexion phases. Performance was assessed using three-dimensional kinematic data and ground reaction forces. A significant main effect of the preparatory condition was observed for the jump take-off time. Pairwise comparisons revealed that the jump take-off time was 3.4-4.4% faster when initiated during the knee flexion phase than the no-prep condition and the extension phase (p = .028). Increasing lower-limb loading and downward body movement with knee flexion appeared to facilitate effective loading to take-off to reach the high target and faster downward-directed take-off to reach the low target, respectively. Pre-jump knee flexion movement could be utilised by soccer goalkeepers to facilitate faster take-off to maximise their chances of saving shots within the reach of single-leg side-jumping.